Applied General Equilibrium Analysis of Renewable Energy Policies - d'Artis Kancs (Economics and Econometrics Research Institute (EERI), 2007)
In this paper we develop an applied general equilibrium framework for assessing socio-economic impacts of alternative renewable energy policies and apply it to the bioenergy sector. The policy scenarios are assessed in a comparative static analysis. The numerical simulation results allow us to assess and compare welfare and distributional impacts of alternative renewable energy policies. Our empirical findings suggest that the bioenergy sector in Poland would benefit most from an indirect tax reduction. According to our simulation results, reducing the fossil energy sectors' subsidies would be the second best policy option.
Keywords: O13; P28; Q21; Q23; Q28; Q42; 330; Applied General Equilibrium; CGE; Renewable Energy; Bioenergy